The world of WAP. - Wilhelm, Kathy (Far Eastern Economic Review, 2000)
It is now possible to explore what the world of Wireless Application Protocol (WAP) has to offer before subscribing to the service. The easiest way to do this is to use a personal computer and the wired Web. This is possible because a number of software developers have created websites with programs called emulators that enable people to visit WAP sites right from their PC. Details of a number these sites as well as of WAP sites that are not exclusive to a single operator and that can be accessed from a WAP-enabled handset are provided.